Treatment indications for antidepressants prescribed to pregnant women: A population‐based descriptive study from Denmark. Issue 3 (23rd January 2020) - Liu, Xiaoqin; Musliner, Katherine L.; Agerbo, Esben; Ingstrup, Katja G.; Sun, Yuelian; Yu, Yongfu; Munk‐Olsen, Trine
Abstract: Purpose: Antidepressants are the mainstay of pharmacological treatment for nonpsychotic mental disorders in the perinatal period. However, little is known about the indications for antidepressant use during pregnancy. We aimed to examine the treatment indications of antidepressant prescriptions redeemed by pregnant women and to investigate whether treatment indication patterns changed over time. Methods: We conducted a population‐based descriptive study using Danish national registers. We identified pregnancies resulting in live births between 2006 and 2016 from the Medical Birth Registry. We linked them to the National Prescription Registry to extract information on antidepressant prescriptions during pregnancy. We used generalized estimating equations to examine whether the indication patterns of antidepressants changed over time. Results: A total of 47 093 antidepressant prescriptions associated with 17 170 pregnancies were identified. Overall, 82.3% of pregnancies received antidepressant prescriptions for depression, including 9.2% of pregnancies affected by comorbid indications, mainly anxiety disorders. In addition, 11.5% of pregnancies received prescribed antidepressants for anxiety disorders only, 3.8% for insomnia only, 0.5% for anxiety and insomnia, and 1.9% for other disorders. There was a small decrease in the percentage of antidepressant prescriptions for depression from 2006 to 2016, with an adjusted 1‐year risk difference of −0.4% (95% confidence interval [CI], −0.7% to −0.1%), while the percentage for anxiety disorders increased, and the adjusted 1‐year risk difference was 0.9% (95% CI, 0.7% to 1.1%). Conclusion: The majority of antidepressant prescriptions in pregnancy are for depression treatment, which suggests that antidepressant prescription during pregnancy may be a suitable proxy for a depression diagnosis.